Polyester fibres; chemistry and technology / Hermann Ludewig, with the collaboration of Werner Roth [and others] Translated by B. Buck with technical guidance from David M. Jones. - Ludewig, Hermann.
Translation of Polyesterfasern. Chemie und Technologie.